Ground Ice Content and Geochemistry of Active Layer and Permafrost in Northwestern Arctic Canada - Fontaine, Marielle (Université d'Ottawa / University of Ottawa, 2016)
This study aimed to contribute to baseline knowledge of permafrost geochemistry within the uppermost 3-4 m of permafrost at 8 sites on the Peel Plateau and east of the Mackenzie Delta, NWT (67-68oN). The following variables were measured: gravimetric water content (GWC), pore water conductivity (PWC), leachate conductivity (LC), dissolved ions by ICP-AES (i.e. Ca, SO4, Mg, Fe, K, Na, Mn, Cl), organic carbon content (calculated by linear regression from organic matter content), as well as inorganic carbon content (obtained from loss on ignition analysis). PWC was positively correlated to GWC and values were generally at least 5 times less than LC values, likely underestimating total dissolved solutes using the former method. LC increased with depth to reach maximum values below the paleo thaw unconformity (>10 mS/cm). Carbon content typically remained low throughout the cores with the exception of samples associated to the shallow-rooted vegetation cover at the ground surface. Results showed that the active layer, relict active layer and the permafrost below the thaw unconformity can be divided into three statistically significant layers. PCA results indicated some spatial patterns with increasing LC values at greater depth, suggesting that layer geochemical profiles reflect varying degrees of soil chemical weathering processes since the early Holocene.